Earthquake-related chemical and radioactivity changes of thermal water in Kuzuluk-Adapazari, Turkey - Belin, B.; Yaçin, T.; Suner, F.; Bozkurtoğlu, E.; Gelir, A.; Güven, H. (Elsevier BV, 2002)
The movements of the North Anatolian Fault Zone (NAFZ) caused two devastating earthquakes within an 87-day interval, epicentered on Gölcük-Izmit (17 August, 1999) and Düzce-Bolu (12 November, 1999). The Kuzuluk geothermal area (KGA) is located in the middle of the epicenters and the distance between the geothermal area and the fault zone is less than 5 km. Hot water samples were collected from two thermal boreholes that supply hot water to the Kuzuluk thermal complex. The water samples taken prior to and after earthquakes were analysed by Neutron Activation and Atomic Absorption Spectroscopy. Particularly, increase in total a and total beta activities, in the content of Pb, Cr, Ni, Cu and decrease in the content of Fe, Zn, Cd, Mn, and Co are significant. The highest values are 75, 35, 12 and 65 ppb for Pb, Cr, Ni and Cu, respectively. The lowest values are 45, 55, 15, 135 and 6 ppb for Fe, Zn, Cd, Mn and Co, respectively.
Keywords: Disasters; Radioisotopes; Hot Temperature; Turkey; Metals, Heavy; Spectrophotometry, Atomic; Water